An Effect of Relationship Marketing On Customer Trust and Impact on Customer Retention Bank Sumut Branch Lubuk Pakam - Rifky Budi Setiawan (Budapest International Research and Critics University, 2021)
In retaining customers, PT. Bank Sumut applies the strategy of Relationship Marketing owned by each transaction. This can result in the higher trust of customers in the bank. The implication to this condition is that Bank needs to harmonize the competency, technology, and resources owned with the needs and wants of the customers. With the application of Relationship Marketing, PT. Bank Sumut can retain its customers (Customer Retention). Relationship Marketing is all of the marketing activities directed to build, develop and retain a successful relational exchange. The data for this descriptive quantitative survey study were obtained through distributing questionnaires to 85 respondents. The data obtained were analyzed through path analysis by using the SPSS program. This paper showed that harmony, acceptance, and participation simplicity simultaneously had a positive and significant influence on Customer Retention. Partially, harmony, acceptance, and participation simplicity have each had a positive and significant influence on Customer Retention. Harmony, acceptance, and participation simplicity simultaneously had a positive and significant influence on the trust of customers. Partially, harmony and acceptance had a positive and significant influence on the trust of customers while participant simplicity did not have a positive and significant influence on the trust of customers. The trust of customers had a positive and significant influence on Customer Retention. Respectively, harmony, acceptance, and participation simplicity indirectly had a positive influence on Customer Retention through the trust of customers at PT. Bank Sumut Lubuk Pakam Branch.